Influence of Psychosocial Characteristics on Social Media Usage among Continuing Education Learners (Cels) in Kwara State University, Malete, Nigeria - Yusuf, Murtala Akanbi; Yunusa, Abdullhai Abubakar; Sulaiman, Kabir Alabi; Adeyemi, Ismail Olatunji (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
In line with the growing incursion/adoption of social media into teaching and learning, this study was conducted to understand continuing education learners’ psycho-social characteristics and their influence on their social media. A quantitative research design approach using an online Google form with 388 participants was adopted. Descriptive statistics, t-test and ANOVA were used. Results revealed that the students mostly used Facebook as their major social media platform for connecting with friends and family along with WhatsApp, Twitter, and Instagram. In addition, the study revealed that learners with higher self-concept and socioeconomic status are more inclined to social media usage among CELs. It is believed that the knowledge of psychosocial characteristics of CELs on their usage of social media will inform a bespoke and purposeful curriculum planning, design and implementation that optimizes the achievement of the learning objectives for different classes of the students based on their psycho-social differences. Abstrak Sejalan dengan semakin maraknya penggunaan/adopsi media sosial ke dalam proses belajar mengajar, penelitian ini dilakukan untuk memahami karakteristik psiko-sosial peserta didik pendidikan lanjutan dan pengaruhnya terhadap media sosial mereka. Pendekatan desain penelitian kuantitatif menggunakan formulir Google online dengan 388 peserta diadopsi. Statistik deskriptif, uji-t dan ANOVA digunakan. Hasil penelitian menunjukkan bahwa sebagian besar siswa menggunakan Facebook sebagai platform media sosial utama mereka untuk terhubung dengan teman dan keluarga bersama dengan WhatsApp, Twitter, dan Instagram. Selain itu, penelitian ini mengungkapkan bahwa pelajar dengan konsep diri dan status sosial ekonomi yang lebih tinggi lebih cenderung menggunakan media sosial di kalangan CEL. Diyakini bahwa pengetahuan tentang karakteristik psikososial CELs dalam penggunaan media sosial mereka akan menginformasikan perencanaan, desain, dan implementasi kurikulum yang dipesan lebih dahulu dan bertujuan yang mengoptimalkan pencapaian tujuan pembelajaran untuk kelas siswa yang berbeda berdasarkan perbedaan psiko-sosial mereka.